Light and electron microscopic studies on testicular development in swamp buffalo bulls (Bubalus bubalis) - Nordin, W.; Azmi, T. I.; Bongso, T. A. (1986)
The epithelium of seminiferous tubules of immature Malaysian swamp buffalo bulls from 6 months to 32 months of age was studied by light and transmission electron microscopy with a view to determining the structural features in the seminiferous tubules that could possibly contribute towards an exceptionally long period of attainment of sexual maturity in this species. Prior to 12 months of age the seminiferous tubules were solid cords. The epithelium of the seminiferous tubules consisted of undifferentiated Sertoli cells and spermatogonia. Although spermatocytes were present they did not develop further into spermatids and thus they degenerate due to the absence of mature Sertoli cells. Spermatogenesis began at 15 months of age accompained by canalization of the seminiferous tubules. From 15 months through to 32 months, although the epithelium of the seminiferous tubules possessed all the features of mature seminiferous tubules, the characteristic wavy appearance of spermatozoa in the lumina of the seminiferous tubules which is an indicator of the presence of mature and motile spermazoa was still lacking in these tubules.